On (b,c)-system at finite temperature in thermo field approach - Abdalla, MCB; Gadelha, A. L.; Vancea, IV (Elsevier B.V., 2000)
We construct the finite temperature field theory of the two-dimensional ghost-antighost system within the framework of thermo field theory. (C) 2000 Elsevier B.V. B.V. All rights reserved.